Depresi dan Kesepian Pada Lanjut Usia Saat Pandemi COVID-19 : Depression and Loneliness in the Elderly During the COVID-19 Pandemic - Esti Widiani; Nurul Hidayah; Abdul Hanan (NERS Jurnal Keperawatan, 2022)
The ongoing COVID-19 pandemic has had a psychological impact on the elderly. The elderly are prone to experiencing psychosocial problems or mental disorders when isolating themselves or withdrawing from community activities, one of which is the COVID-19 pandemic. They can feel lonely and depressed. Spirituality is needed by the elderly to face the pandemic. This study aims to determine the relationship between spirituality with depression and loneliness in the elderly. This research was conducted with a cross-sectional approach using a questionnaire on 142 elderly respondents. Research respondents were taken by purposive sampling technique. Based on the Spearman rank correlation test results, there is no relationship between spirituality scores and depression scores with a value of p=0.939 (p>0.05). There is a direct relationship between spirituality with a p-value of 0.00 (p <0.05). The correlation coefficient value between spirituality score and loneliness score is 0.306, which means that the higher the spirituality score, the higher the loneliness score with low relationship strength. Spirituality is not the only factor that can improve depression and loneliness in the elderly during the COVID-19 pandemic. Other aspects need to be identified to help overcome depression and loneliness in the elderly.